KONSEP BESI DALAM Q.S. AL-HADID AYAT 25 BERDASARKAN TEORI VERIFIKASI AlFRED JULES AYER - Humairoh, Melisa (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
This study examines the concept of iron in Q.S. Al-Hadid verse 25 by applying A.J. Ayer’s verification theory, which emphasizes empirical validation of meaningful statements. The verse describes iron as a divine gift endowed with strength and utility for humanity. Using qualitativse methods and thematic interpretation, the research analyzes whether the Quranic claim about iron can be empirically verified according to logical positivism. Findings suggest that the mention of iron aligns with modern scientific knowledge, particularly in astrophysics and chemistry, such as iron’s extraterrestrial origin and its vital role in human life. However, metaphysical aspects in the verse remain unverifiable through Ayer’s strict criteria. The study highlights the potential epistemological bridge between religious scripture and empirical science, offering a foundation for interdisciplinary dialogue. This approach enriches the understanding of Quranic verses from both theological and scientific perspectives.